Efektivitas Teknik Visual Schedule Dalam Meningkatkan Kemandirian Anak Autisme di SLB Negeri 1 Takalar - Chalista Aiska Putri; Mustafa; Dwiyatmi Sulasminah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Independent eating is a crucial self-care skill for children with Autism Spectrum Disorder (ASD); however, many still rely on assistance from teachers or caregivers to complete the steps involved in eating. This study aimed to analyze the effectiveness of the visual schedule technique in enhancing the eating independence of a child with autism at SLB Negeri 1 Takalar. A quantitative approach was employed using a Single-Subject Research (SSR) design (A-B-A), comprising baseline (A1), intervention (B), and baseline (A2) phases. Data were collected through observation and performance testing of a second-grade student with autism and subsequently analyzed using visual descriptive analysis (within-condition and between-condition). The results demonstrated that the implementation of the visual schedule progressively improved eating independence across all observed indicators. This improvement was evidenced by a positive trend, an increase in skill level, and a 0% overlap percentage, indicating a strong intervention effect. The acquired skills were maintained during the second baseline phase, despite a slight decline following the cessation of the intervention. Thus, the visual schedule technique is effective in fostering eating independence in children with autism and serves as a viable, structured self-care instructional strategy to support the development of daily living skills in a school setting.